Physical Activity Patterns on Quality of Life in Chronic Kidney Failure Patients With Hemodialysis: Literature Review - Zeferino Ximendes de Almeida; Sutrisno Sutrisno; Dedi Saifullah (PT. Griya Eka Sejahtera, 2020)
Background: Patients with chronic kidney failure require appropriate therapy to optimize kidney function. This therapy is not a drug, but as a substitute for kidney function. Renal function replacement therapy, such as hemodialysis is a routine medical treatment for chronic kidney disease. Method: The research design used a systematic use of several research journal articles published on the basis of Health. the health databases used include: Google Scholar, the national library and Pubmed with a time span of 2012 to 2020. Results: The results of this study are that there is an influence of physical activity patterns on the quality of life of patients with chronic kidney failure with hemodialysis. Conclusion: Patients with chronic kidney failure who undergo long-term hemodialysis therapy often feel worried about unpredictable disease conditions and disturbances that occur in life due to the disease they are experiencing. The patient's mindset changes because there are activities the patient does besides thinking about his illness